Future of education in the Caribbean : report of first consultation (CARICOM Secretariat GeorgetownGY, 1989)
Describes the context of the Caribbean Education System. Highlights areas of concern in education touching on literacy, numeracy, and foreign language teaching. Discusses educational planning with emphasis on curricula, teacher education, administration and communication. Considers the implications of innovations in measurement and evaluation practices for teacher education.
IDS